Partial Trisomy 4p Recombinant Chromosome 4 Caused By Pericentric Inversion Of Paternal Origin - Talavera-Vargas-Machuca, Sergio (2015)
The partial trisomy 4p, usually originated from translocations between chromosome 4 and other non-homologous chromosomes or pericentric inversion of chromosome 4, causing abnormal chromosome gametes between normal and the inverted one, yielding a recombinant chromosome duplication can carry small ami segments (4p) or the long arm (4q) the latter being non-viable. The phenotypic characteristics of this condition present with severe mental retardation, delayed psychomotor development, craniofacial anomalies, strabismus, musculoskeletal defects, heart defects, cryptorchidism and micropenis. We describe the case of a 1-year 6-month child with delay in psychomotor development and dysmorphic features, having a recombinant 4p duplication of paternal origin. It is the first case of duplication 4p found in our institution due to hereditary, it is necessary to perform counseling to parents and monitoring of the proband for therapeutic and psychological management.